"Health is Wealth": Valuing Health in the Nineteenth-Century United States. Issue 3 (28th November 2019) - Kiechle, Melanie A
Abstract: This essay traces the evolution of the motto "health is wealth" from its origins as an anticapitalist argument made by antebellum sanitary reformers to its acceptance as a fundamental principle of organized public health in the United States. Sanitarians originally coined the phrase "health is wealth" to counter the capitalist maxim "labor is wealth." Because city leaders were businessmen who understood economic arguments, public health reformers increasingly gave health a monetary value in order to win over this audience and change urban governance. Although "health is wealth" momentarily co-opted the logic of capitalism in order to successfully make the case for institutionalizing public health within municipal and state governments, the phrase ultimately wrote economic values into the purpose and functions of public health boards and departments. In the course of advancing a proactive public health that prevented both endemic and epidemic diseases, sanitarians reduced the perception of health from a common good to a commodity. The economic logic employed by early reformers is critical, not only for understanding how the long reach of early American capitalism touches us today but also for recognizing that modern public health functions in the way it was created, as a capitalist system.